The feats of brave awaiting (On monograph «Komsomol Phenomenon: the middle of the 1950s – the first half of the 1960s») - R. V. Rybakov (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the monograph «The Komsomol Phenomenon: the middle of the 1950s – the first half of the 1960s». The peculiarities of the author’s approach in covering the youth past are revealed. An attempt is made to analyze the most important laws of the development of the Komsomol identified by a team of researchers. A scientific, methodological novelty, some aspects that require, in the opinion of the author, further study are noted